Synthesis of hetarylsubstituted pyrazolo[3,4-c] isoquinolines under Pictet—Spengler reaction conditions - Bogdan, N.M.; Borodkin, Ya.S.; Sujkov, S.Yu.; Khairulin, A.R.; Bogza, S.L. (Reports of the National Academy of Sciences of Ukraine, 2018)
The synthesis and reactions of 1 and 3-hetaryl-substituted 5-aminopyrazoles with aldehydes under the Pictet—Spengler reaction conditions have been studied. It has been shown that the possibility of formation and yields of pyrazolo [3,4-c] isoquinoline derivatives essentially depends on the structure and location of the heterocyclic substituent in the pyrazole core.